Perspectives on the Role of a Central Bank - Mancera, Miguel (International Monetary Fund, 1991)
This book presents the proceedings of a conference held in Beijing, China, on the role of central banks. Among the speakers were Paul A. Volcker, Miguel Mancera, and Jean Godeaux. The paperss review the role of monetary policy, its formulation and implementation, the supervision and regulation of financial systems, and the structure and responsibilities of central banks. The book is jointly published, both in English and Chinese, by the People's Bank of China, the IMF, and the UNDP.